Assessing the applicability of the long-chain diol (LDI) temperature proxy in the high-temperature South China Sea. (June 2020) - Yang, Yi; Ruan, Xiaoyan; Gao, Chao; Lü, Xiaoxia; Yang, Huan; Li, Xuejie; Yao, Yongjian; Pearson, Ann; Xie, Shucheng
Highlights: The LDI proxy is calibrated for the tropics using South China Sea surface sediments. LDI values are negatively correlated with SST at temperatures above 27 °C. This new LDI calibration is well correlated with archaeal lipid temperature proxies. Abstract: The Long-chain Diol Index (LDI) is a palaeotemperature proxy applied to marine sediments up to Miocene in age. Recent studies have revealed that the LDI-inferred temperature yields significant errors in waters >27 °C. This necessitates further assessment of the performance of the LDI proxy in high-temperature marine regimes. For this purpose, we collected 58 surface sediment samples from the tropical South China Sea (SCS), where annual sea surface temperature (SST) ranges from 24 °C to 29 °C. The original LDI calibration yields temperatures <27 °C for these samples, and the residual between the LDI-inferred temperature and the measured SST (ΔT) increases (to >4 °C) as SST increases. This ΔT, or mis-calibration, is significantly correlated with the measured SST as the temperature increases above 27 °C. This relationship also exists in sediment trap data. We therefore re-calibrated the LDI-inferred temperature to generate a new relationship that can be applied to environments with SST >27 °C, which is beyond the range of the original LDI proxy. Both the recalibrated LDI and, for comparison, archaeal lipid temperature proxies were applied in the high-temperature SCS; the improved correlation shows the LDI recalibration could be applied to palaeo-records from tropical oceans.